GW24-e0608 The relationship between interval of two contrast exposure during cardiac catheterisation and contrast induced nephropathy. (1st October 2013) - Yuanhui, Liu; LIU, Yong; Chen, Ji-yan; Chen, jin; Chen, Shao-hui; Ye, Piao; Ning, Tan
Abstract : Objectives: It is not clear that the interval of two contrast exposure duringcardiac catheterisation may affect contrast induced nephropathy. We assumed that the risk of CIN increased when two contrast exposure during cardiac catheterisation are perfumed in short interval, without enough time for recovery from the adverse effects of repeated contrast exposure. Methods: We prospectively observed 137 patients undergoing second cardiac catheterisation, which were divided into two groups with the interval ≤ 7 days and > 7 days. CIN was defined as an increase in serum creatinine of ≥ 0.5 mg/dl or ≥ 25% relatively from the baseline within 48-72 h after contrast media exposure. Results: Eighteen patients (13.1%) developed CIN. The patients with the interval ≤ 7 days (interval median: 3, interquartile range: 2–4) have the similar baseline creatinine and contrast volume with the patients with the interval > 7days (interval median: 59, interquartile range: 28-152) (baseline SCr:86 ± 24vs89 ± 18, p = 0.344; dose of CM: 133 ± 58 vs 102 ± 57, p = 0.067, respectively). The incidence of CIN is no significant different between two groups (14.4% vs 10.6%, p = 0.531). Conclusions: Risk of CIN is not influenced by the interval of two contrast exposure during cardiac catheterisation. Our results do not support the notion of short interval may affect contrast induced nephropathy.